Pemberdayaan Ekonomi Petani Karet melalui Inovasi Produk dari Pelepah Daun Pinang : Economic Empowerment of Rubber Farmers through Product Innovation from Areca Palm Leaf Sheaths - Hendy Endarwan; Gary Putra Etwanto (Jurnal Bisnis dan Ekonomi, 2025)
Abstract : This study explores the economic empowerment of smallholder rubber farmers through product innovation using areca palm leaf sheaths as eco-friendly raw materials. Objective : To strengthen the economic resilience of smallholder rubber farmers through community-based innovation, promoting value-added utilization of agricultural waste and integrating local enterprises into sustainable value chains. Methodology : A qualitative descriptive approach combined with participatory action research (PAR) was employed to analyze the process, impact, and community involvement in this empowerment program. Data were collected through observation, interviews, focus group discussions, and documentation of field activities in Musi Banyuasin, South Sumatra. Research Results : The program successfully trained over 30 farmers and established a community production unit capable of producing more than 200 units of eco-tableware. The initiative increased household income by 20–30%, improved livelihood capital, and reduced environmental waste through the conversion of organic residues into biodegradable products. Farmers demonstrated high enthusiasm and independence in production, supported by local cooperatives. The activity also opened potential export opportunities and contributed to circular economy practices, reinforcing sustainable supply chains within the rubber industry. Keywords : economic empowerment, rubber farmers, community innovation, areca leaf sheath, circular economy, sustainability